Observatory operations : strategies, processes, and systems III : 30 June-2 July, 2010, San Diego, California, United States - Silva, David R.; Peck, Alison B.; Soifer, B. Thomas; American Astronomical Society; Society of Photo-optical Instrumentation Engineers (Bellingham, WA : SPIE)
Includes bibliographical references and author index